The Effect of Pointer Finger Friction (PFF) Massage on β-Endorphin Levels and Sleep Quality of Postpartum in Semarang - Rahayu, Sri; Runjati, Runjati (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: In Asia, more than 54.7% of postpartum mothers experience sleep deprivation, ranging from 50.9%. Massage can increase the levels of endorphins in the body and stimulate the central nervous system (CNS). This study aimed to determine the effect of Pointer Finger Friction (PFF) Massage on β-Endorphin Levels and Sleep Quality in Postpartum Mothers in Semarang City.Method: This study was quasi-experimental with a pre-posttest control group design. The population consisted of postpartum mothers in the Semarang City Health Center area, and samples were obtained by simple random sampling. The number of samples were 36 postpartum mothers who were divided into 2 groups. The treatment in the intervention group with PFF was carried out five times, starting on the first postpartum day. Venous blood was collected before and after treatment to measure endorphin levels and sleep quality. Data analysis was performed using the Mann–Whitney U test.Result: The results of the study showed most of the respondents were 23 years old and had a high school education (82.9%). The average level of β-endorphins after the treatment group was 135 mg/ml higher than that of the control group (38 pg/ml), and the quality of sleep after the treatment group decreased by 3.5 compared to the control group, with a score of 0.9. There was a relationship between the levels of β-endorphins and sleep quality between the PFF and control groups. To increase the levels of β-endorphins and the quality of sleep of postpartum mothers, we can promote and educate people about the use of the PFF massage method.